Autonomous parafoil flaring control system for eVTOL aircraft - Doran, Stephen; Souanef, Toufik; Whidborne, James F. (MDPI, 2025)
Reducing landing kinetic energy during emergency landings is critical for minimising occupant injury in eVTOL aircraft. This study presents the development of an autonomous parafoil control system for impact point targeting and flare control. A model predictive controller for a six-degree-of-freedom parafoil and eVTOL payload model was designed incorporating an inner-loop flare controller for descent speed-based flare height adjustments and an outer-loop nonlinear model predictive control (MPC) to minimize line-of-sight error. Two guidance methods were explored: a standard fixed impact point approach and an adaptive method that adjusts the target point dynamically to account for horizontal travel during flaring. The standard method outperformed the uncontrolled system in 79.64% of cases, while the adaptive method achieved success in 40.73% of scenarios, with both methods maintaining vertical landing velocities below 8 m/s in all tested cases. Controller performance degraded under higher wind speeds and large control derivative variations, with the adaptive method position error attributed to flare distance estimation inaccuracies.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4010 Engineering Practice and Education; 4001 Aerospace engineering; adaptive guidance; eVTOL; impact point targeting; landing position error; landing velocity; line of sight; model predictive control; nonlinear control; parafoil; six degrees of freedom